The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.neubiorev.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress, air pollution, inflammation, and disease: An integrative review and immunologic model of social-environmental adversity and lifespan health

Abstract: Socially disadvantaged individuals are at greater risk for simultaneously being exposed to adverse social and environmental conditions. Although the mechanisms underlying joint effects remain unclear, one hypothesis is that toxic social and environmental exposures have synergistic effects on inflammatory processes that underlie the development of chronic diseases, including cardiovascular disease, diabetes, depression, and certain types of cancer. In the present review, we examine how exposure to two risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 214 publications
(262 reference statements)
3
69
0
1
Order By: Relevance
“…Despite these limitations, this longitudinal study with a large representative sample of oncology patients is the first to evaluate for associations among SLEs, general stress, cancer-specific stress, and the use various coping strategies and greater morning and evening fatigue severity during CTX. In addition, prior research has identified that higher levels of SLEs may decrease a patient's participation in health-related behaviors (e.g., physical activity) [55], which may affect adherence to exercise interventions prescribed to decrease fatigue severity. Additional studies are needed that evaluate the effect of stress management strategies and interventions targeted at the use of disengagement coping strategies to mitigate morning and evening fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, this longitudinal study with a large representative sample of oncology patients is the first to evaluate for associations among SLEs, general stress, cancer-specific stress, and the use various coping strategies and greater morning and evening fatigue severity during CTX. In addition, prior research has identified that higher levels of SLEs may decrease a patient's participation in health-related behaviors (e.g., physical activity) [55], which may affect adherence to exercise interventions prescribed to decrease fatigue severity. Additional studies are needed that evaluate the effect of stress management strategies and interventions targeted at the use of disengagement coping strategies to mitigate morning and evening fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…A 3-level urbanicity score was derived from classifications from 2011 census data, which combined residential density, output area, and contextual data (592 of 1858 participants with available data [31.9%] lived in the most urban settings at 18 years of age). Analyses controlled for a range of potential covariates that might confound the association 43 between air pollution and adolescent psychotic experiences, including family socioeconomic status, 44 family psychiatric history, 45 , 46 maternal psychosis, 47 , 48 childhood psychotic symptoms, 22 , 49 adolescent smoking, 47 cannabis dependence, 47 alcohol dependence, 47 neighborhood socioeconomic status, 50 neighborhood crime, and neighborhood social conditions. 51 , 52 , 53 , 54 , 55 All covariates are described in detail in the eMethods in the Supplement .…”
Section: Methodsmentioning
confidence: 99%
“…In turn, this chronic social stress leads to a greater risk of pulmonary illness (26). Overall, these mechanisms can influence each other and strongly impact postnatal growth and pubertal development, leading to a reduced maximal lung function (13,27).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%